Mucoepidermoid Carcinoma of Minor Salivary Glands - Tinoco, Paulo; Pereira, José Carlos Oliveira; Filho, Rodolfo Caldas Lourenço; Brito, Thiego Silveira Cajubá; Pereira, Betina Mameri; Carrara, Vânia Lúcia; Godoy, Sueliana Marta F. (Arquivos Internacionais de Otorrinolaringologia, 2011)
Introduction: The Mucoepidermoid Carcinomas (MEC) represent about 5% of all tumors in the salivary glands. It is an aggressive lesion and must be considered as a diagnosis hypothesis in the oral mucosa proliferative lesions. The early diagnosis and the correct management of this neoplasm are key factors for the prognosis. Wide local resection and eventually postoperative radiotherapy is the choice treatment.Objective: To report the case of a patient with mucoepidermoid carcinoma of oral cavity, exteriorizing through the mouth and being submitted to surgical exeresis and radiotherapy that evolved to death on the fourth month from beginning of the treatment.Case Report: CT, 47 years old, white woman was forwarded to the ORL service of the HSJA after a critical bleeding episode in oral cavity. She reported the appearing of a mass with fast and expansive growth in a topography of canine fossa for +/- 06 months, associated to the loss of 10 kg. Patient dehydrated, pale with pediculated tumoration of +/- 06 cm, firm consistency, painless upon palpation and bleeding. Chronic alcoholic and smoker. Non-palpable cervical lymph nodes. Faced with the case we opted for a surgical resection of the tumor and the performance of histopathological exam that confirmed mucoepidermoid carcinoma of minor salivary glands. The patient was sent to the radiotherapy service; but she abandoned the treatment and evolved with death 4 months after.Final Comments:In this case, the fast and aggressive growth of the lesion, the size of the tumor and the abandonment of the proposed treatment was determinant for the patient's prognosis.
Keywords: mucoepidermoid tumor; minor salivary glands; mouth